2013
DOI: 10.1371/journal.pone.0073596
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin-Releasing Hormone (TRH) Promotes Wound Re-Epithelialisation in Frog and Human Skin

Abstract: There remains a critical need for new therapeutics that promote wound healing in patients suffering from chronic skin wounds. This is, in part, due to a shortage of simple, physiologically and clinically relevant test systems for investigating candidate agents. The skin of amphibians possesses a remarkable regenerative capacity, which remains insufficiently explored for clinical purposes. Combining comparative biology with a translational medicine approach, we report the development and application of a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 73 publications
3
64
0
Order By: Relevance
“…However, it is unlikely that the putative anti-aging effects of THs can be explained by wound healing inhibition. THs actually promote wound healing, a highly energy-consumptive process, in murine skin in vivo (Kassem et al, 2012;Safer, 2012;Safer et al, 2005) and promotes reepithelialization in experimentally wounded organ-cultured human skin (Meier et al, 2013) ex vivo (Paus lab, unpublished observation), while mice devoid of the TR-alpha and -beta show retarded wound-healing (Contreras-Jurado et al, 2014;Safer et al, 2005). Moreover, all in situ analyses reported here where purposely performed distant from the periphery of the organ-cultured skin fragments, thus lowering the risk to confound aging-related phenomena with superimposed wound M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 healing processes (for detailed discussion of wound healing-related skin responses as a potential confounding element in the current study, see Supplementary Text S1).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, it is unlikely that the putative anti-aging effects of THs can be explained by wound healing inhibition. THs actually promote wound healing, a highly energy-consumptive process, in murine skin in vivo (Kassem et al, 2012;Safer, 2012;Safer et al, 2005) and promotes reepithelialization in experimentally wounded organ-cultured human skin (Meier et al, 2013) ex vivo (Paus lab, unpublished observation), while mice devoid of the TR-alpha and -beta show retarded wound-healing (Contreras-Jurado et al, 2014;Safer et al, 2005). Moreover, all in situ analyses reported here where purposely performed distant from the periphery of the organ-cultured skin fragments, thus lowering the risk to confound aging-related phenomena with superimposed wound M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 healing processes (for detailed discussion of wound healing-related skin responses as a potential confounding element in the current study, see Supplementary Text S1).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Previous researches conducted in different organisms such as humans, pig and frog demonstrated that skin organ culture was successfully maintained for several days, without any structural changes. These findings show that skin organ culture can be used for testing chemical compounds and for investigating different physiological and pathological conditions (Varani et al, 2007;Dame et al, 2008;Jacques et al, 2010;Lebonvallet et al, 2010;Kleszczyński and Fischer, 2012;Meier et al, 2013).…”
Section: Discussionmentioning
confidence: 78%
“…In the present study the potential Cd-induced stress responses were examined in adult amphibian P. bergeri skin using an ex-vivo full-thickness skin organ culture as the experimental model to study cellular and molecular stress responses. Amphibian organ culture has been used extensively as a valid biological tool for many research issues (Monnickendam and Balls, 1973;Van Rooij et al, 2010;Groot et al, 2012;Meier et al, 2013). Currently, in vitro cultures are being used in both cytotoxic risk assessment and for field evaluation of toxic environmental contaminants.…”
Section: Discussionmentioning
confidence: 99%
“…Scleraxis is a key transcription factor which is recognized essential for tenogenic and ligamentogenic differentiation. Similarly, collagen fibers are ubiquitous macromolecular assemblies in nature, which form structures that support tensile mechanical loads within the human body [110]. Thus, aligned type I collagen fibers are considered more workable primary structural motif for tendon and ligament regeneration.…”
Section: Tendon and Ligament Regenerationmentioning
confidence: 99%
“…Therefore, construction of complex and challenging biomaterials, may improve the mechanical function of tendons and ligaments. Further, potential for tailoring and manipulating the interactions between collagen fibers and biological systems, as hybrid biomaterialbiological assemblages, will help to develop novel tissue engineering strategies for tendon and ligament regeneration [110]. However, semitendinosus tendon can regenerate after being harvested in its whole length and thickness for anterior cruciate ligament (ACL) reconstruction, but it is not applicable to make a neo-tendon.…”
Section: Tendon and Ligament Regenerationmentioning
confidence: 99%